Implementasi Marketing MIX Dalam Upaya Peningkatan Penjual Butik Muslimah Di Kota Tanjung Pura - Isnaida Isnaida; Muhizar Muchtar; Muhammad Arfan Harahap (Al-Sharf: Jurnal Ekonomi Islam, 2022)
The purpose of this research is to find out how the implementation of marketing mix in an effort to increase sales at Muslimah Tanjung Pura boutiques. The type of research used in this research is the qualitative type using descriptive analysis methods. Data collection is done through observation, structured interviews or interviews, and documentation. The results of this study show that the Muslimah Boutique "Emma Collection" has implemented a marketing mix in running its business. Starting with planning, developing and releasing their products by following the trend of every time the latest Muslim fashion model production among the community. In addition, in the Muslim fashion store "Emma Collection" is carried out promotion by installing banners / brands in front of the store, through social media, namely Facebook and Blackberry Masengger. From the results of research on this promotion, it can be concluded that it is in accordance with the theory of promotion that should be done in a business. From the price aspect in the Muslimah Boutique store "Emma Collection" has determined the price of each product by taking into account well. Muslimah boutique "Emma Collection" does not take advantage of many times, and the price is affordable by students and the surrounding community.